Field Validation of a Non-carcinogenic and Eco-Friendly Disinfectant in a Stand-In Footbath for Treatment of Footrot Associated With aprV2-Positive Strains of Dichelobacter nodosus in Swiss Sheep Flocks - Schmid, Robin Michael; Steiner, Adrian; Becker, Jens; Baumberger, Sandra; Dürr, Salome; Alsaaod, Maher (Frontiers in Veterinary Science, 2022)
A national control program for virulent footrot is currently planned in Switzerland. Since commonly used disinfectants either contain heavy metals or are carcinogenic, the aim of this study was to verify the effectiveness of an eco-friendly and non-carcinogenic candidate disinfectant against aprV2-positive strains of Dichelobacter nodosus. Additionally, the effect of the selective use of long-acting oxytetracyclines was evaluated. A total of 18 farms with confirmed footrot infection, randomly allocated to two treatment groups: 1) with antibiotics (AB; n = 9) and, 2) no antibiotics (NAB; n = 9), were included. Claws were carefully trimmed and scored using a scale from 0 (clinically healthy) to 5 (complete loss of the horn capsule) and a prewash waterbath was implemented on 11 farms. Twice-weekly, repeated whole-flock stand-in footbaths with the candidate disinfectant (6%) were performed. Additionally, animals of group AB with a score >= 3 were administered oxytetracyclines by injection. On all farms, at ten days after last treatment, aprV2-positive strains could not be detected by risk-based sampling for real-time PCR analysis after 7 to 21 (median = 12) footbaths with a minimal culling rate of non-responders on nine farms. Farms without contact to other sheep remained without clinical signs of footrot for a minimum of 245 days (mean ± standard deviation: 293.6 ± 23.6). Antibiotic treatment did not reduce the number of footbaths needed. In contrast, a mean of 3.3 disinfecting footbaths could be saved by implementing a prewash waterbath. At animal level, individual and selective use of oxytetracyclines lead to a higher chance (odds ratio = 9.95; 95% CI: 3.54-27.95; p < 0.001) for a lesion score >= 3 to improve to a lesion score < 3 within two weeks compared to treatment without antibiotics. The test disinfectant is an effective and eco-friendly alternative for the planned Swiss footrot control program and selective use of oxytetracycline has a beneficial impact on the recovery of animals with lesion scores >= 3.